CHALLENGES OF TERTIARY EDUCATION IN LIBERIA AND POSSIBLE SOLUTIONS - Sumaworo, Mory D.A (European Scientific Journal, ESJ, 2015)
Liberia as a post- conflict zone faces lots of challenges, but atop of which is preparing reliable and productive human capital through which abundant natural resources that it has can be beneficial and help to change its status of underdevelopment. Further, among negative aftermaths of the 14 years of Civil Wars (1989-2003) in Liberia, is massive migration of professionals and qualified teachers and universities lecturers to the western world mainly the United States of America. Thus, this migration left an adverse effect on pre-university studies in Liberia. As a result, tertiary education has been also dangerously affected. Despite the international and national efforts to revive and rejuvenate educational sector in Liberia, the situation seems to be facing multiple challenges, especially the higher education. Besides, the weakness in Liberian education system has led the President herself, a Noble Price laureate, her Excellency Madam Ellen Johnson Serleaf to describe Liberia education as a mess. Moreover, poor implementation of educational policies, ill - financial supports for institutions of higher learning, poor educational infrastructures, and rampant child labour etc., are some of major things that constitute challenges to higher education in Liberia. Nonetheless, there have been lots of attempts and practical endeavors to reform and refine pre-university school system in Liberia. Subsequently, sophisticate tertiary ones for development and building productive human capitals by the government and her local and international partners, such as The United States International Aid (USAID), The World Bank, the International Monetary Fund (IMF), the African Development Bank, A.S Charitable Society, ( a local NGO) Catholic Schools, Methodist Schools ( local school systems) and others. Therefore, this article aims at looking at challenges facing tertiary education in Liberia and how could they be mitigated and minimized so that the system should be the best after being the mess.